Effects of green manure planting on soil organic carbon in China: A meta-analysis - Shi, Yudi; Tai, Kenong; Cui, Yongwei; Zhang, Ruifang; Li, Xuguang; Ji, Yanzhi; Yin, Baozhong (International Journal of Agricultural and Biological Engineering, 2025)
Growing green manure, as a sustainable agricultural practice, is widely recognized for its role in improving soil structure and enhancing soil quality. However, despite the significant benefits of green manure, research on how its application specifically influences soil organic carbon content remains insufficient, especially in the context of complex and ever-changing agricultural management models and ecological environments. In this study, 59 papers published from January 1980 to May 2024 were collected, and a database containing 299 groups of comprehensive effects of green manure planting on soil organic carbon content and crop yield, as well as its key regulatory factors, through a meta-analysis system. The research is mainly conducted through several key elements types of green manure, planting seasons, fallow periods of food crops, soil types, climate types, and planting years. The results show that compared with not growing green manure on fallow land, the cultivation of green manure significantly increased the soil organic carbon content (by 6.98%) and the yield of the next staple food crop (by 10.36%). In different planting seasons, both summer and winter planting of green manure can effectively increase the soil organic carbon (SOC) content and crop yield. Among them, the application effect during the fallow period of wheat and rice is particularly significant, while during the fallow period of maize, only the SOC content increases significantly. From the perspective of green manure types, both the single species of leguminous and the mixed species with cruciferous have shown good effects. The research also found that under soil types such as loam and clay loam, as well as climatic conditions like temperate continental climate, temperate monsoon climate, and subtropical monsoon climate, the effect of green manure planting on the increase of SOC and yield is more significant. In addition, the planting years are also an important influencing factor. Green manure planting for ≤3 a or >5 a can significantly improve the SOC content and crop yield. These findings provide important theoretical support for the scientific application and promotion of green manure in China.Keywords: green manure, soil organic carbon, grain yield, meta analysisDOI: 10.25165/j.ijabe.20251805.9709Citation: Shi Y D, Tai K N, Cui Y W, Zhang R F, Li X G, Ji Y Z, et al. Effects of green manure planting on soil organic carbon in China: A meta-analysis. Int J Agric & Biol Eng, 2025; 18(5): 198–204.